The Implementation of Kirkpatrick Evaluation Model in Financial Management Training - Nazella Putri Wijaya; Metha Djuwita Supriatna (Institute of Computer Science (IOCS), 2022)
Evaluation of the training program is one of the important stages in the implementation of the training program. Evaluation of the training program is carried out with the aim of assessing the level of success or effective and efficiency of all aspects in the training program. Evaluation of the training program at the BPSDM of DKI Jakarta Provincial was carried out using the Kirkpatrick evaluation model at the reaction level. In the evaluation of the training program at BPSDM of DKI Jakarta, it was found that there were still problems in the program evaluation that was not optimal. This research was conducted using qualitative methods with data collection using interview techniques. The data is analyzed using a fishbone diagram, so can get the root of the problem. Based on the results, there are no SOP related to the evaluation, the evaluation system hasn't been updated, lack of awareness of organizers, evaluators and participants. To optimize the evaluation of training programs at BPSDM DKI Jakarta, it can be done: 1) Develop Standard Operating Procedures (SOP) for Program Evaluation; 2) Develop an evaluation system; 3) Provide guidance for participants in the palatia program; 4) Provide training for organizers and evaluators.